2017
DOI: 10.1103/physrevlett.119.077201
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Perpendicular Magnetic Anisotropy by Oxygen Octahedral Rotations in (La1xSrxMnO

Abstract: Perpendicular magnetic anisotropy (PMA) plays a critical role in the development of spintronics, thereby demanding new strategies to control PMA. Here we demonstrate a conceptually new type of interface induced PMA that is controlled by oxygen octahedral rotation. In superlattices comprised of La1−xSrxMnO3 and SrIrO3, we find that all superlattices (0≤x ≤1) exhibit ferromagnetism despite the fact that La1−xSrxMnO3 is antiferromagnetic for x >0.5. PMA as high as 4×10 6 erg/cm 3 is observed by increasing x and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
91
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 49 publications
9
91
1
Order By: Relevance
“…2). Our previous studies have shown the excellent unit-cell layering of the superlattices by using transmission electron microscopy 22,27 . All samples were electrolytically gated with the ionic liquid DEME + -TFSIon the film surface, and voltages were applied across the electrolyte using electrical contacts to the top electrode and film surface ( Figure 1a).…”
Section: Synthesis Of Digital Superlattices and Reference Filmsmentioning
confidence: 99%
“…2). Our previous studies have shown the excellent unit-cell layering of the superlattices by using transmission electron microscopy 22,27 . All samples were electrolytically gated with the ionic liquid DEME + -TFSIon the film surface, and voltages were applied across the electrolyte using electrical contacts to the top electrode and film surface ( Figure 1a).…”
Section: Synthesis Of Digital Superlattices and Reference Filmsmentioning
confidence: 99%
“…The PMA also leads to an anomalous Hall effect [132]. To shed light on the underlying mechanism, Yi et al recently performed a systematic study of the interfacial anisotropy by preparing a series of La 1−x Sr x MnO 3 /SrIrO 3 superlattices with doping ratio x ranging from 0 to 1 [58]. The PMA was shown to emerge at x = 0.5 and then increases rapidly with x.…”
Section: Exploiting Interfacial Coupling Between 5d and 3d States Formentioning
confidence: 99%
“…For instance, emergent ferromagnetism and topological Hall effect have been reported in the SrMn 4+ O3/SrIr 4+ O3 [10][11][12] (SMO/SIO) and La0.7Sr0.3MnO3 (LSMO)/SIO 13,14 heterostructure, respectively. Moreover, through atomically control of the coupling between the iridate and manganite, a tunable in-plane ferromagnetic anisotropy characterized by both magnetization and anisotropic magnetoresistance (AMR) was reported at the La1-xSrxMnO3/SIO 15,16 heterostructures. Up to now, while interesting results have been achieved at the Mn 4+ /Ir 4+ or Mn 3+/4+ /Ir 4+ interfaces, little study explores the perovskite interfaces of pure Mn 3+ and Ir 4+ , which has a unique polar/nonpolar structure.…”
Section: Introductionmentioning
confidence: 99%